Recent developments in peptidomics for the quali-quantitative analysis of food-derived peptides in human body fluids and tissues. (August 2022) - Caira, Simonetta; Picariello, Gianluca; Renzone, Giovanni; Arena, Simona; Troise, Antonio Dario; De Pascale, Sabrina; Ciaravolo, Valentina; Pinto, Gabriella; Addeo, Francesco; Scaloni, Andrea
Abstract: Background: Various bioactive peptides are present in foods and food protein hydrolysates, or are generated in the stomach/intestine of organisms after digestion of dietary proteins. Those resisting gastrointestinal degradation can exert local effects in the gut or systemic effects in the organism body as result of their transport across the intestinal epithelium in the bloodstream, and subsequent adsorption in various organs. For most of these molecules, no concentration data regarding body fluids/tissues are available; this information is essential to rationalize their bioavailability and putative bioactivity. Scope and approach: The main purpose of this study is to provide an exhaustive overview of the bioactive food-derived peptides identified in the gastrointestinal tract, blood, body tissues, urine, breastmilk and feces of animal models or humans fed specific diets, as well as a description of the adsorption mechanisms and metabolic processes eventually affecting their fate. Untargeted and targeted peptidomic methods used for their quali-quantitative description are also reported, together with recent technological advances that have partially solved various analytical challenges in this research field and have disclosed future promising scenarios in nutrition and physiology. Key findings and conclusions: Available information emphasizes that organism tissues/body fluids are pervaded of food-derived species resulting from the digestion of dietary proteins, including some already proved having a specific biological activity. For some for which blood concentration was measured, ascertained data highlight levels in the nanomolar range, which are lower than those generally used for in vitro functional assays. Conversely, few peptides have shown concentration values compatible with a substantial molecular bioavailability and a putative bioactivity. Thus, it remains uncertain if the presence of bioactive food-derived peptides in the body fluids/tissues can be associated with a significant functional effect. Accordingly, the actual study of these exogenous peptides in the human body is more relevant than ever, with the ultimate aim of tangling the complex relationship between diet and health. Highlights: Food-derived bioactive peptides were identified in body fluids/tissues of human/animal models. Information was prominent for gastointestinal aspirates, blood, urine, milk and feces. Peptidomics suffers of specific limitations compared to other holistic approaches. Recent technological advances have opened this scientific field to innovative studies. Quantitative studies will verify peptide levels compatible with a possible corresponding bioactivity.